VIDEO ANIMASI MEMPENGARUHI PENGETAHUAN DAN SIKAP MASYARAKAT MENGENAI PENCEGAHAN STIGMA KEPADA PASIEN TB PARU (Jurnal Kesehatan Siliwangi, 2021)
Disease Pulmonary TB in Indonesia reached 568,987 cases (Ministry of Health, 2020), in West Java it reached 73,285 cases (Jabar's Riskesdas, 2018), Subang Regency 3,226 cases (Subang Health Office, 2020). Stigma becomes an obstacle in controlling pulmonary TB which affects the delay in diagnosis and treatment adherence. Health education is needed by the community to eliminate stigma and increase knowledge. This study aims to determine and analyze the effect of health education through animated videos on people's knowledge and attitudes about preventing stigma against pulmonary TB patients. Research design with One Group Pretest Posttest Design Without Control. The research subjects were 62 people in one of the working areas of the Public Health Center in Subang Regency. The data of this study came from the results of the knowledge and attitude questionnaire. This study shows that animated video media can increase knowledge, seen from the average value of knowledge before being given animated videos (51.61%) and after (90.81%). While the attitude of the research subjects who supported the prevention of stigma was given animated video media as many as 29 people (47%) and after being given animated video media attitudes that supported as many as 42 people (68%). The results of the paired sample t-test knowledge questionnaire Sig value is obtained. (2-tailed) of 0.000 < 0.005 and the results of thetest Wicolxon attitude questionnaireobtained the value of Sig. (2-tailed) of 0.000. So that there is an influence of animated video media on people's knowledge and attitudes about preventing stigma against pulmonary TB patients. Recommendations for further researchers can develop animated video media for stigma prevention and determine the appropriate age range of respondents in the study.